Understanding Elderly Health in Riau: Phenomenology Study on Healthcare Access, Chronic Diseases, and Care Challenges - Gusman Virgo; Indrawati; Sri Hardianti (Postgraduate, University of Mataram, 2025)
Despite recent improvements in health indicators, ensuring affordable, quality healthcare for the elderly in Riau Province remains challenging. This study examines personal experiences accessing healthcare services, costs, barriers, and strategies to develop more effective solutions for elderly welfare. We conducted a qualitative phenomenological study with 20 seniors in Riau Province (November-December 2024) with equal gender representation. Experienced interviewers gathered information about healthcare seeking, accessibility, affordability, and strategies. Data were analyzed using thematic analysis. Results revealed unsatisfactory health conditions among elderly populations, with many suffering from benign tumors, chronic kidney disease, persistent pain, and gastric ulcers. Most participants had multiple non-communicable diseases, particularly diabetes and hypertension. The elderly faced significant obstacles accessing both government and private healthcare, including inadequate facilities, long wait times, complicated referral systems, and limited medication and medical personnel availability. Financial constraints presented major barriers, especially for private services with high costs. Limited understanding of procedures and additional expenses further complicated access. Transportation issues and lack of awareness about available services highlighted the need for targeted interventions to improve health outcomes in this demographic. System improvements and service enhancements are necessary for optimal healthcare access. Policymakers and elderly care providers must prioritize elderly-friendly healthcare infrastructure with affordable care costs to improve health conditions among senior citizens in Riau Province.